Stiffness and aamping response associated with shock attenuation in downhill running - Chu, J. J.; Caldwell, G. E. (Journal of Applied Biomechanics, 2004)
Studies on shock attenuation during running have induced alterations in impact loading by imposing kinematic constraints, e.g., stride length changes. The role of shock attenuation mechanisms has been shown using mass-spring-damper (MSD) models, with spring stiffness related to impact shock dissipation. The present study altered the magnitude of impact loading by changing downhill surface grade, thus allowing runners to choose their own preferred kinematic patterns. We hypothesized that increasing downhill grade would cause concomitant increases in both impact shock and shock attenuation, and that MSD model stiffness values would reflect these increases. Ten experienced runners ran at 4.17 m/s on a treadmill at surface grades of 0% (level) to 12% downhill. Accelerometers were placed on the tibia and head, and reflective markers were used to register segmental kinematics. An MSD model was used in conjunction with head and tibial accelerations to determine head/arm/trunk center of mass (HATCOM) stiffness (K1), and lower extremity (LEGCOM) stiffness (K2) and damping (C). Participants responded to increases in downhill grade in one of two ways. Group LowSA had lower peak tibial accelerations but greater peak head accelerations than Group HighSA, and thus had lower shock attenuation. LowSA also showed greater joint extension at heelstrike, higher HATCOM heelstrike velocity, reduced K1 stiffness, and decreased damping than HighSA. The differences between groups were exaggerated at the steeper downhill grades. The separate responses may be due to conflicts between the requirements of controlling HATCOM kinematics and shock attenuation. LowSA needed greater joint extension to resist their higher HATCOM heelstrike velocities, but a consequence of this strategy was the reduced ability to attenuate shock with the lower extremity joints during early stance. With lower HATCOM impact velocities, the HighSA runners were able to adopt a strategy that gave more control of shock attenuation, especially at the steepest grades.